Medicine: A debate on building society - Falla-Martínez, María Carolina (2023)
The purpose of this letter to the editor is to discuss the role of doctors in transforming social and political realities, particularly in Colombia. The premise is that the environment has a significant impact on the health of patients, and therefore, doctors should take a more active role in understanding and discussing political and social realities. This article is a reflective piece motivated by the current situation we find ourselves in, both as a society and at a personal level. The changes we are experiencing demand a more active role from us, as doctors, in the social construction of our communities. Rather than simply labeling actions as good or bad, we must encourage more critical and practical thinking about the reality of our country, which faces more challenges now than ever before due to the pandemic. Throughout the text, I propose an open conversation that does not require taking a specific position, but instead encourages us to ask ourselves how we can better adjust our knowledge to the reality of our patients. Let us start by acknowledging the need to know more.